Utilization of breast cancer screening in Kenya: what are the determinants? - Antabe, Roger (BMC Health Serv Res, 2020)
BACKGROUND: Breast cancer accounts for 23% of all cancer cases among women in Kenya. Although breast cancer screening is important, we know little about the factors associated with women’s breast cancer screening utilization in Kenya. Using the Andersen’s behavioural model of health care utilization, we aim to address this void in the literature. METHODS: We draw data on the Kenya Demographic and Health Survey and employ univariate, bivariate, and multivariate analyses. RESULTS: We find that women’s geographic location, specifically, living in a rural area (OR = 0.89; p < 0.001) and the North Eastern Province is associated with lower odds of women being screened for breast cancer. Moreover, compared to the more educated, richer and insured, women who are less educated, poorer, and uninsured (OR = 0.74; p < 0.001) are less likely to have been screened for breast cancer. CONCLUSION: Based on these findings, we recommend place and group-specific education and interventions on increasing breast cancer screening in Kenya.